Polska adaptacja Kwestionariusza Źródeł Pewności Siebie w Sporcie (SSCQ-PL) – geneza teoretyczna oraz badanie pilotażowe właściwości psychometrycznych - Gazdowska, Zuzanna; Ryszkiewicz, Maja; Parzelski, Dariusz (Journal of Education, Health and Sport, 2015)
Gazdowska Zuzanna, Ryszkiewicz Maja, Parzelski Dariusz. Polska adaptacja Kwestionariusza Źródeł Pewności Siebie w Sporcie (SSCQ-PL) – geneza teoretyczna oraz badanie pilotażowe właściwości psychometrycznych = Polish adaptation of Sources of Sport-Confidence Questionnaire (SSCQ-PL) theoretical background and pilot study of psychometric properties. Journal of Education, Health and Sport. 2015;5(10):207-220. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32743 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A207-220 https://pbn.nauka.gov.pl/works/662374 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Polska adaptacja Kwestionariusza Źródeł Pewności Siebie w Sporcie (SSCQ-PL) – geneza teoretyczna oraz badanie pilotażowe właściwości psychometrycznych Polish adaptation of Sources of Sport-Confidence Questionnaire (SSCQ-PL) theoretical background and pilot study of psychometric properties Zuzanna Gazdowska – SWPS Uniwersytet Humanistycznospołeczny / SWPS University of Social Sciences and Humanities Maja Ryszkiewicz - SWPS Uniwersytet Humanistycznospołeczny / SWPS University of Social Sciences and Humanities Dariusz Parzelski - SWPS Uniwersytet Humanistycznospołeczny / SWPS University of Social Sciences and Humanities Słowa kluczowe: pewność siebie, źródła sportowej pewności siebie, samoocena, własna skuteczność. Key words: self-confidence, sources of sport-confidence, self-esteem, self-efficacy. Streszczenie Celem artykułu jest przedstawienie założeń teoretycznych leżących u podstaw Kwestionariusza Źródeł Pewności Siebie w Sporcie SSCQ-PL. Narzędzie to służy do pomiaru źródeł sportowej pewności siebie rozumianej jako pewność sportowca, która związana jest ze świadomością tego, że posiada umiejętności i zdolności, aby osiągnąć sukces w swojej dyscyplinie (Vealey, 1998). Niniejsza publikacja ukazuje etapy dokonywania językowo-kulturowej adaptacji Kwestionariusza SSCQ do warunków polskich. Przedstawiono również wyniki badania właściwości psychometrycznych, nowo powstałego narzędzia, takich jak trafność teoretyczna i kryterialna oraz rzetelność. Na potrzeby badania pilotażowego przebadano 100 osób będących czynnymi sportowcami, zarówno amatorami, jak i zawodowcami. Potwierdzona została rzetelność i trafność teoretyczna adaptowanego Kwestionariusza. Trafność kryterialna narzędzia zbadana poprzez korelacje ze zmiennymi samoocena (kwestionariusz SES) i poczucie własnej skuteczności (kwestionariusz GSES) nie została potwierdzona. Abstract The aim of this paper is to present the theoretical assumptions which form the basis for Sources of Sport-Confidence Questionnaire SSCQ-PL. This Questionnaire is used to measure the sources of sport-confidence understood as the athlete’s confidence, connected with the awareness that s/he has the skills and abilities necessary to achieve the success in own discipline (Vealey, 1998). This publication depicts the primary stages of preparation of the linguistic-cultural adaptation of SSCQ to the Polish conditions. Results of the psychometric properties research (such as the theoretical and criterion validity and reliability) are presented. For the needs of the pilot study, 100 participants were examined. They are active athletes, both amateurs and professionals. The theoretical validity and reliability of adapted Questionnaire were confirmed. Correlation with the SES Questionnaire and GSES Questionnaire did not confirm the criterion validity of the SSCQ-PL.